Perbaikan Kinerja Guru Madrasah Ibtidaiyah: Pelatihanan, Perancangan, dan Pendampingan - Muhammad Yaumi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2018)
The purposes of this study were to increase teachers' understanding of multiple intelligences through learner-centered approach, improve teachers’ performance in designing learner characteristics-oriented instruction, and improve teachers’ performance in implementing instruction. This study used action research by using proactive design involving 26 respondents from 10 elementary Madrasah in Gowa, South Sulawesi and 4 collaborators. The methods of data collection were observation, interview, and test. The collected data were analyzed by using a mixed method (qualitative and quantitative). The results showed that the implementation of training on multiple intelligence based learning proved to increase teachers' understanding of learner centered approach and contribute an average score 32.61% of teachers’ performance improvement, designing multiple intelligences based learning proved to give a contribution of 26.55% to the teachers’ performance improvement, and mentor system proved to give contribution of 23,86% to the teachers’ performance improvement in instructional implementation. It is suggested that the implementation of training should be followed by workshop and training in order to increase teachers’ performance.